1991
DOI: 10.1029/90jc01933
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of sensible and latent heat flux in the western equatorial Pacific Ocean

Abstract: Micrometeorological measurements, including direct eddy‐correlation measurements of heat and moisture fluxes, have been made from shipboard under light‐wind conditions in the western equatorial Pacific warm pool. Air‐sea temperature differences were typically 1.5°–2°C, that is, 1°–1.5°C larger than long‐term averages from merchant ship data. A sea surface “cool skin” of about 0.3°C was observed. Bulk transfer coefficients for both fluxes agree well with the predictions of Liu et al. (1979) in the convective wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
1
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 38 publications
9
77
1
2
Order By: Relevance
“…He mentioned that in the typical case over the western tropical Pacific with a coefficient of 1.8X10-3, the latent heat flux is about 40% higher than the value given by a neutral coefficient of 1.3X10-3. Bradley et al (1989) confirmed the study of Liu et al (1979) from their observation that CD increases as the wind speed becomes weak. To estimate the contribution of (q*(Ts)-qa), we show Fig.…”
Section: Datasupporting
confidence: 81%
“…He mentioned that in the typical case over the western tropical Pacific with a coefficient of 1.8X10-3, the latent heat flux is about 40% higher than the value given by a neutral coefficient of 1.3X10-3. Bradley et al (1989) confirmed the study of Liu et al (1979) from their observation that CD increases as the wind speed becomes weak. To estimate the contribution of (q*(Ts)-qa), we show Fig.…”
Section: Datasupporting
confidence: 81%
“…Furthermore, there is experimental evidence of the increase of C D over water surfaces for weak winds under 5 m/s [58][59][60]. As about 60% of U 10 estimations by Equation (6) during the modeling period fall under such wind conditions, simulation S5 performs the empirical expression proposed by Wuest and Lorke [61]: for U 10 < 5 m/s (14) 4.…”
Section: Wind Stress Formulationsmentioning
confidence: 99%
“…MOS also assumes that the statistics are stationary and horizontally homogenous. Within the boundary layer, and near the surface, turbulent energy is produced mainly by mechanical working of the stresses on the mean velocity gradient and higher up, principally by buoyant motions (Bradley, Coppin et al 1991).…”
Section: Air-sea Interaction Towermentioning
confidence: 99%